The Activation and Restoration of Shame in an Intimate Relationship: A First-Hand Account of Self-Injury - Gunnarsson, Nina Veetnisha (Qualitative Sociology Review, 2021)
This paper is grounded in a first-hand account of my own experiences with self-injury and shame. By using my personal diary entries as support for this account and a sociological framework of shame, I explore the process of shame and shame reactions in an intimate relationship. I illustrate how shame was activated by my internalized critical other, how the shame cycle de-stabilized my relationship, and, finally, how shame was restored through the other’s validation and acceptance, or how it led to more shame managed by self-injury. However, this account is not simply about self-analysis, or a need to indulge in my pain; rather, it is an inner dialogue that rests on the commitment to develop a richer understanding of the personal and interpersonal experiences of self-injury and shame. Today, I finally understand how shame works and this has helped me to not get caught up in my emotions. So, although shame may take a hold of me at times, I am no longer, like before, controlled by my shame.